Development and Analysis of an Innovative Layout Scheme of an Articulated Two-Section Tram Tramcar - Voytkiv, S. V. (Science and Transport Progress, 2023)
Purpose. The main objective of the work is to develop and analyze the optimal layout of an articulated two-section tramcar for the creation of promising competitive models of cars of a significantly higher technical level, as well as to assess the prospects for their mass production provided that the maximum passenger capacity is ensured. Methodology. Based on the analysis of the regulated technical requirements for the dimensional parameters of tramcars, maneuverability parameters and permissible loads on their wheeled bogies, as well as on the analysis of the main technical parameters of existing models of single and two-section tramcars equipped with two biaxial wheeled bogies - body length and curb weight - the permissible length of their bodies and the estimated weight in the equipped state were determined. Two biaxial wheeled bogies were replaced by four uniaxial bogies. Findings. An innovative layout of an articulated two-section tramcar based on the use of four single-axle wheeled bogies and minimization of overhangs of body sections was proposed and developed, provided that the maximum length of a single tramcar and the track of wheeled bogies and the width of the car were preserved. A methodology has been developed for assessing the effectiveness of the proposed design solutions and the comfort of passenger transportation by single and two-section tramcars with two biaxial and four single-axial wheeled bogies, the preliminary designs of which have been developed according to three different layout schemes. Originality. For the first time, a layout of an articulated two-section tramcar is proposed based on an innovative solution - the use of four uniaxial wheeled bogies instead of two biaxial ones. A methodology for analyzing and evaluating the feasibility of using the proposed layout for creating promising models of a two-section tramcar has been developed. Practical value. The choice of an optimal innovative layout scheme with four uniaxial wheeled bogies for the creation of promising competitive models of articulated two-section tramcars with optimized parameters of their body length and nominal passenger capacity with higher passenger comfort compared to existing analog tramcars has been substantiated at the stage of developing draft proposals.